Engineering Solutions to Cotton Ginning Problems - Dadajanov Arafatali Komiljanovich (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
Cotton processing plays a pivotal role in Uzbekistan’s agricultural-industrial integration, with technological advancements becoming increasingly vital for maintaining fiber quality. The ginning process, a key operation in cotton processing, often suffers efficiency losses due to moisture-induced fiber damage and mechanical wear of saw drums, particularly during autumn when cotton arrives with high humidity. Traditional ginning machines lack mechanisms to prevent raw roll formation, leading to fiber degradation and frequent downtime, with insufficient research focused on eliminating this core issue without compromising productivity. This study aims to develop an engineering solution that enhances the ginning process by addressing moisture-related challenges and mechanical limitations through a newly designed device. The proposed device eliminates the formation of raw rolls, increases fiber separation efficiency by over 30%, and extends the life span of saw drums by threefold. Additionally, it reduces downtime and energy consumption while improving fiber grade, ultimately increasing profitability. Unlike conventional ginning systems, the device integrates an optimized working chamber structure and innovative fiber cleaning mechanisms such as a drum grate with checkerboard-patterned needle heights, enhancing impurity removal without fiber loss. These innovations provide practical, cost-effective upgrades suitable for Uzbekistan’s cotton enterprises, aligning scientific research with industrial needs and promoting sustainable productivity gains. The study reinforces the value of industry-academia collaboration in generating adaptive technologies for context-specific agricultural challenges.